Incidencia de abortos con serología positiva a neospora caninum en bovinos lecheros en el distrito de moche, departamento La Libertad - Sánchez Ubillús., Luis Alberto (2014)
The bovine Neosporosis is a parasitic disease caused by Neospora caninum, a protozoan that has acquired great importance to have reached important worldwide prevalence rates, and to be involved as one of the major causative agents of abortion in dairy beef cattle. This research was carried out with the objective of determining the incidence of abortions with positive serology to Neospora caninum in dairy bovines of the District of Moche, La Libertad. The study was based on analysis of blood serum, 96 blood samples that were collected of dairy cattle females (milk cows and heifers) those antecedents have presented abortion troughout their life production were evaluated. The ELISA technique was used to detect and quantify the specific antibodies to tachyzoites of Neospora caninum. In data analysis, it was found that the 64.58% of the animals that aborted, showed positive serology to Neospora caninum, where heifers presented higher seropositivity with 77.74%. It was observed that abortions produced in third and the fifth months of gestation are the ones that had increased frequency of seropositivity, being of 29.03% in both months. In addition, second-lactation cows presented higher frequency of abortions, 41.67%, with positive serology to Neospora caninum and that the dogs are not directly related to the results of seropositives bovines to Neospora caninum.